2020
DOI: 10.1016/j.hydromet.2020.105367
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction of intra-lanthanides using a mixture of TBP and TODGA in ionic liquid

Abstract: In this study, we have investigated the solvent extraction of yttrium(III) and lanthanide(III) ions from nitric acid solutions in an organic phase consisting of a mixture of two electrically neutral extractants, namely tri-n-butyl phosphate(TBP) and N,N,N',N'-tetra(n-octyl)diglycolamide (TODGA). We employed hydrophobic room-temperature ionic liquid 1-methyl-3-butyl-imidazolium bis(trifluoromethanesulfonyl)imide as more environmentally benign diluent as compared to conventional molecular solvents. The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…A mixture of trivalent lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) can be separated into individual elements contained in nitric acid solution by using a solution of extractants-tri-(n-butyl) phosphate (TBP) and N,N,N′,N′-tetraoctyldiglycolamide (compound 13) in ionic liquid 3, which is more environmentally friendly than conventional molecular solvents [18]. It was found that Ho, Er, Tm, Yb, and Lu are most effectively extracted using the above system.…”
Section: Lanthanidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture of trivalent lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) can be separated into individual elements contained in nitric acid solution by using a solution of extractants-tri-(n-butyl) phosphate (TBP) and N,N,N′,N′-tetraoctyldiglycolamide (compound 13) in ionic liquid 3, which is more environmentally friendly than conventional molecular solvents [18]. It was found that Ho, Er, Tm, Yb, and Lu are most effectively extracted using the above system.…”
Section: Lanthanidesmentioning
confidence: 99%
“…It should be noted that in the above-mentioned works [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], separation of REEs from impurities of heavy and alkaline earth metals Fe (III), Pb (II), Ti (IV), Cu (II), Mg (II) and others as well as thorium Th (IV) contained in rare earth ores was not investigated.…”
mentioning
confidence: 99%
“…Another important point that should not be ignored is the transfer of IL ions from the diluent to the aqueous phase, in this case either [omim] + or [Tf 2 N] − . Recent works 28,31,32 have pointed out that, when using conventional extractants in IL diluents, the cation or the anion of these diluents could undergo ion exchange stoichiometry with the subsequent transfer of IL ions to the aqueous phase. However, according to Eqn (9), the extraction of perrhenate anions is accompanied by the extraction of protons while maintaining the charge neutrality of the aqueous phase, and therefore there would not be a transfer of either [omim] + or [Tf 2 N] − to the aqueous phase.…”
Section: Extraction Of Re(vii)mentioning
confidence: 99%
“…[1][2][3][4] Nevertheless, the unwanted burden of the loss of ionic components to the aqueous phase in the case of traditional imidazolium based ionic liquids ultimately reduces the meritorious impact of ionic liquids over molecular solvents. [1][2][3][4][5][6][7][8][9][10] To address this issue, long alkyl chain quaternary ammonium such as methyltrioctylammonium ([N 1888 ] + ) or phosphonium such as trihexyl(tetradecyl)phosphonium ([P 66614 ] + ) based ionic liquids have shown their potentiality in the metal ion recovery since they are highly hydrophobic and sustainable (reusability and recyclability) in nature. This essen-tially allows them to restrict the loss of ionic liquid cations to the aqueous stream during the extraction process.…”
Section: Introductionmentioning
confidence: 99%